1999
DOI: 10.1074/jbc.274.53.37995
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Part of the Functional Epitope for Ligand Binding on the Receptor for Urokinase-type Plasminogen Activator by Site-directed Mutagenesis

Abstract: The urokinase-type plasminogen activator receptor (uPAR) 1 is a multifunctional membrane glycoprotein primarily involved in the regulation of pericellular proteolysis due to its high affinity interaction with the growth factor-like module of urokinase-type plasminogen activator (uPA) (1), but which has also been implicated in the promotion of cell adhesion due to its vitronectin and integrin binding properties (2), in signal transduction (3) and chemotaxis (4, 5). However, the uPA-uPAR interaction per se is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 56 publications
(88 reference statements)
2
90
0
Order By: Relevance
“…In contrast, Tyr 57 is located at the bottom of the hydrophobic uPA binding cavity and is completely shielded from solvent in the corresponding uPAR-ATF complex (16,40). The affinity of uPAR Y57A for uPA is accordingly decreased by ϳ7-fold compared with both uPAR wt and uPAR W32A (34,39), whereas vitronectin binding is unaffected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Tyr 57 is located at the bottom of the hydrophobic uPA binding cavity and is completely shielded from solvent in the corresponding uPAR-ATF complex (16,40). The affinity of uPAR Y57A for uPA is accordingly decreased by ϳ7-fold compared with both uPAR wt and uPAR W32A (34,39), whereas vitronectin binding is unaffected.…”
Section: Resultsmentioning
confidence: 99%
“…Purified mouse anti-uPAR mAbs (1 g/ml) were covalently immobilized on a carboxymethylated dextran matrix (CM5 sensor chip) using N-hydroxysuccinimide/N-ethyl-NЈ- [3-(diethylamino)propyl] carbodiimide, yielding levels of 400 -1000 RU-immobilized mAbs (39). To establish the kinetics for the mAb-uPAR interactions, serial 2-fold dilutions of purified human uPAR (0.4 -200 nM in running buffer) were analyzed at 20°C with 50 l/min flow rates.…”
Section: Hek293 Cells Expressing Upar Wt and Selected Mutants-mentioning
confidence: 99%
“…The uPA binding site within uPAR has been studied extensively in the past several years, using a number of different approaches (15)(16)(17)(18). In good agreement with the published data, we found that the uPA binding site occupies a broad region that encompasses all three domains, with the most critical residues located in D1 and D2.…”
Section: Discussionmentioning
confidence: 99%
“…These domains fold into a central 3-stranded ␤-sheet and a globular, disulfide-rich core (14). The uPA binding site within uPAR has been studied extensively using a number of different approaches, including site-directed photoaffinity labeling, chemical cross-linking, alanine scanning, as well as synthetic peptides, and the functional residues have been located within the ␣-helix and the three connecting loops, especially the second and third loops of all three domains (13,(15)(16)(17)(18). In contrast to the well characterized uPA binding site, the Vn binding site within uPAR remains elusive.…”
mentioning
confidence: 99%
“…Although the N-terminal domain I of uPAR contains major determinants for uPA-binding, high affinity interaction with uPA is dependent on the multidomain structure of the receptor, indicating that all three protein domains are involved in the formation of a composite ligand binding site (Ploug, 1998;Gårdsvoll et al, 1999;Bdeir et al, 2000). In contrast, uPA binds to uPAR via a defined continuous peptide sequence …”
Section: Introductionmentioning
confidence: 99%